Regioselective Access to 1, 2‐Diarylhistidines through the Copper‐Catalyzed N1‐Arylation of 2‐Arylhistidines. Issue 5 (6th February 2017) - Sharma, Krishna K.; Mandloi, Meenakshi; Jain, Rahul
Abstract : We report the copper(I)‐catalyzed synthesis of 1, 2‐diarylhistidines through the N1‐arylation of protected 2‐arylhistidines in the presence of 8‐hydroxyquinoline as a ligand and aryl iodides as electrophilic coupling partners under microwave irradiation at 140 °C. This method provides regioselective access to previously inaccessible multisubstituted histidines with intact chirality in high yields. The synthesized 1, 2‐diarylated histidines are a hitherto unknown class of derivatives with untapped potential in modified amino acid based peptide and peptidomimetic drug discovery. Abstract : The Cu I ‐catalyzed synthesis of 1, 2‐diarylhistidines through the N1‐arylation of protected 2‐arylhistidines in the presence of 8‐hydroxyquinoline as a ligand and aryl iodides as electrophilic coupling partners under microwave irradiation at 140 °C is presented. This method provides regioselective access to previously inaccessible multisubstituted histidines with intact chirality in high yields.